1998
DOI: 10.1016/s0006-3495(98)77507-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Origin of the L-Type Ca2+ Current of Skeletal Muscle Myotubes Selectively Deficient in Dihydropyridine Receptor β1a Subunit

Abstract: The origin of Ibetanull, the Ca2+ current of myotubes from mice lacking the skeletal dihydropyridine receptor (DHPR) beta1a subunit, was investigated. The density of Ibetanull was similar to that of Idys, the Ca2+ current of myotubes from dysgenic mice lacking the skeletal DHPR alpha1S subunit (-0.6 +/- 0.1 and -0.7 +/- 0.1 pA/pF, respectively). However, Ibetanull activated at significantly more positive potentials. The midpoints of the GCa-V curves were 16.3 +/- 1.1 mV and 11.7 +/- 1.0 mV for Ibetanull and Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
26
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 45 publications
6
26
0
Order By: Relevance
“…Because quantification of the ␣ 1S protein expression in the mouse myotube-typical peripheral couplings was never performed, a clear differentiation between non-functional ␣ 1S expression and functional ␣ 1S expression in the membrane (charge movement) was not feasible. Thus, the ␤ 1a -induced facilitation of ␣ 1S charge movement was not detected in the mouse system and consequently experimental attempts on the ultrastructural level were not pushed forward (14,17,18). Due to the lack of these essential informations, the data of a large series of ␤-expression experiments (24, 25, 49 -52) were in general interpreted in a way that domains of the DHPR ␤ 1a subunit, similar to elements present in the ␣ 1S subunit, might be directly involved in activation of RyR1 channels (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because quantification of the ␣ 1S protein expression in the mouse myotube-typical peripheral couplings was never performed, a clear differentiation between non-functional ␣ 1S expression and functional ␣ 1S expression in the membrane (charge movement) was not feasible. Thus, the ␤ 1a -induced facilitation of ␣ 1S charge movement was not detected in the mouse system and consequently experimental attempts on the ultrastructural level were not pushed forward (14,17,18). Due to the lack of these essential informations, the data of a large series of ␤-expression experiments (24, 25, 49 -52) were in general interpreted in a way that domains of the DHPR ␤ 1a subunit, similar to elements present in the ␣ 1S subunit, might be directly involved in activation of RyR1 channels (26).…”
Section: Discussionmentioning
confidence: 99%
“…␤ subunits of voltage-gated Ca 2ϩ channels were repeatedly shown to be responsible for the facilitation of ␣ 1 membrane insertion and to be potent modulators of ␣ 1 current kinetics and voltage dependence (15,16). Whether the loss of EC coupling in ␤ 1 -null mice was caused by decreased DHPR membrane expression or by the lack of a putative specific contribution of the ␤ subunit to the skeletal muscle EC coupling apparatus (17,18) was not clearly resolved. Recently, other ␤-functions were identified in skeletal muscle using the ␤ 1 -null mutant zebrafish relaxed (19,20).…”
mentioning
confidence: 99%
“…Using molecular biology, protein biochemistry, and immunocytochemistry techniques, we show that the zebrafish mutant relaxed lacks the DHPR ␤ 1a subunit. In contrast to previous studies (8,11), we can use this novel model organism to demonstrate that the ␣ 1S is correctly targeted into skeletal muscle triad junctions in the absence of ␤ 1a . However, DHPRs lacked the skeletal muscle-specific arrangement in tetrads and displayed substantially reduced charge movement.…”
mentioning
confidence: 84%
“…So, how does the lack of the ␤ 1a protein affect expression and function of the DHPR in skeletal muscle? Based on extensive coexpression experiments in heterologous systems (31,32) and on results from the ␤ 1a -null mouse (8,11), a lack of ␣ 1S triad expression would have been expected. However, immunofluorescence analysis of the fully differentiated zebrafish myotubes clearly demonstrated that ␤ 1a deficient cells are able to correctly target ␣ 1S into the triads (Fig.…”
Section: ) Statistical Significance Was Determined By Using the ⌬Cmentioning
confidence: 99%
See 1 more Smart Citation